Institutional Factors for Anti-Corruption Climate in Modern Russian Society - Melnikov, Evgeniy Gennadievich; Miletskiy, Vladimir Petrovich; Savin, Sergey Dmitrievich (Calitatea Vieții, 2019)
The paper addresses system-based sociological methodology and considers the anti-corruption policy in the modern Russian society. The authors try to identify key institutional factors for creating anti-corruption climate in the context of advanced transformations. It is noted that modern Russia should develop the anti-corruption climate applying both Soviet and foreign experience. The paper concludes that the key role in the process under analysis is given to maintaining the adequate Russian conditions for the anti-corruption law-based climate providing the execution of the whole set of norms of the positive law by the social subjects and the law institutes. This includes such law-based regulation mechanisms as judicially relevant activities and other law-enforcement practices suitable for reproduction and improvement of the anti-corruption climate at all levels of the powerful hierarchy. Promotion of the anti-corruption behavioral standards, the development of the respective law-oriented consciousness and law culture should also be paid special attention to.